AI AND DRONES IN AGRICULTURE : inovation and sustainability in agribusiness - Balabenute, Bianca; Filho, João de Lucca (Revista Interface Tecnológica, 2024)
Population growth presents the challenge of producing more food while minimizing the impact on the environment. Technology has stood out for the transformations, innovations and sustainability that have emerged in the agricultural sector. This article explores the impact of integrating artificial intelligence (AI) with drones in agriculture. The objective of the study is to analyze the main applications of AI and drones, such as crop monitoring, livestock management, input applications and pest identification, and how these practices contribute to increasing productivity, reducing costs and acting on conservation environmental. The methodology includes a literature review and an analysis of case studies that illustrate the use of these technologies in different agricultural contexts. The results show that the addition of AI and drones in agriculture allows for more efficient management of natural resources, greater precision in decision-making and the implementation of sustainable agricultural practices. As a conclusion, it was suggested that, despite the technical and economic challenges, the use of AI and drones has the potential to revolutionize agribusiness, making it more competitive and environmentally responsible.
Keywords: Artificial Intelligence.; Drones.; Agribusiness; Sustainability; Precision agriculture